A combined photovoltaic and novel renewable energy system: An optimized techno-economic analysis for mining industry applications. (15th April 2017) - Vyhmeister, Eduardo; Aleixendri Muñoz, Cristina; Bermúdez Miquel, José Miguel; Pina Moya, Javier; Fúnez Guerra, Carlos; Rodríguez Mayor, Lourdes; Godoy-Faúndez, Alex; Higueras, Pablo; Clemente-Jul, Carmen; Valdés-González, Héctor; Reyes-Bozo, Lorenzo
Abstract: The productivity of the mining industry in Chile, currently the main driver of Chilean economy, is closely tied to foreign demand for ores. Ore-processing is known for involving energy–intensive processes, such as comminution, concentrating and cathodic processes. As mining activities take place in the arid north of Chile, they are affected by water scarcity. Water shortage has forced the industry to pump desalinated seawater up to mining sites over 2000 m above sea level, further increasing electricity consumption. Given these energy needs, and the fact that electrical energy supply in the north of Chile is based on fossil fuels, it is important to consider the use of renewable energies as environment-friendly and economic alternatives. The aim of this work is to evaluate, by an optimized techno-economic analysis, the use of photovoltaic and a novel wind-based technology to supply at least 10% of the current and the predicted electrical energy requirements of the mining industry in the Antofagasta region. A combination of an optimization problem and technical evaluation was performed using Matlab to obtain the optimal number of solar and wind-based technology units in a case study. Total energy generation from a novel wind-based technology unit is 67, 616 MWh/y, corresponding to 14.45·10 6 Nm 3 (1298 t) of hydrogen and 7.41·10 6 Nm 3 (10, 323 t) of oxygen after electrolytical transformation. Considering a 65% efficiency of the combined cycle fed with hydrogen and oxygen, 28, 133 MWh/y of electrical energy would be obtained. For the cases studied the cost of energy from the combined system was estimated to be between 0.255 US/kWh and 0.273 US/kWh, slightly higher than the average energy regional cost. According to the analysis, the renewable energy system could be a sustainable alternative to supply economic green energy to the mining industry in Chile. Graphical abstract: Highlights: Chilean mining industry needs electrical energetic supply based on green energies. A hybrid system (photovoltaic and a novel wind-based technology) was evaluated. Currently energy and the optimized hybrid systems have similar energy costs. Novel renewable energy system would allow greener copper mining operations.